Design and Development of a Teaching Factory (TeFa) Information System in Chlorine Digital Media Company to Support Vocational High School Entrepreneurship Programs - Cepi Prananda; Rony Setiawan (Jurnal Pendidikan Indonesia, 2025)
This study designs and develops a web-based Teaching Factory (TeFa) information system for Chlorine Digital Media Company to enhance vocational high school entrepreneurship programs, supported by Indonesia’s Ministry of Education. Addressing manual inefficiencies in TeFa operations, the research employs direct observation, literature review, and UML-based system analysis to create a solution featuring product recording, turnover monitoring, and SWOT-driven business feasibility assessments. Key findings reveal improved data accuracy, real-time collaboration among students, teachers, and industry partners, and automated certificate generation—bridging gaps in existing systems. The system’s success underscores its potential to elevate workforce readiness and entrepreneurial skills, with implications for scalable adoption across vocational fields. Future research directions include AI and IoT integration and longitudinal impact studies on employability.